2018
DOI: 10.1186/s12938-018-0587-0
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal MRI-based classification of migraine: using deep learning convolutional neural network

Abstract: BackgroundRecently, deep learning technologies have rapidly expanded into medical image analysis, including both disease detection and classification. As far as we know, migraine is a disabling and common neurological disorder, typically characterized by unilateral, throbbing and pulsating headaches. Unfortunately, a large number of migraineurs do not receive the accurate diagnosis when using traditional diagnostic criteria based on the guidelines of the International Headache Society. As such, there is substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 33 publications
0
37
1
2
Order By: Relevance
“…Other CNN methods, including DenseNet121 [22], ResNet101 [23], InceptionV3 [24], VGG19 [25, 26], Modified VGG (MVGG) [27], GoogleNet [9,2830], and SDAE [3133], have also been implemented for comparison with the methods proposed in this paper.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other CNN methods, including DenseNet121 [22], ResNet101 [23], InceptionV3 [24], VGG19 [25, 26], Modified VGG (MVGG) [27], GoogleNet [9,2830], and SDAE [3133], have also been implemented for comparison with the methods proposed in this paper.…”
Section: Resultsmentioning
confidence: 99%
“…ResNet is another efficient CNN architecture [24], and it is used to classify clinical 12 skin diseases in recent times [25]. Inception model is also reported for MRI-based classification of migraine in [26]. VGG architecture of CNN is employed in two-phase multimodel automatic brain tumour diagnosis system [27] and lung nodule classification between benign nodule and lung cancer [28].…”
Section: Related Workmentioning
confidence: 99%
“…Previous studies have found that patients with migraine displayed significant alterations in their cerebral spontaneous activity patterns ( 19 22 ), and acupuncture treatment could effectively regulate the disrupted cerebral functional activity of these patients ( 21 ). Furthermore, the regional cerebral functional activity and the interregional functional connectivity have been detected as the meaningful features for distinguishing patients with migraine from healthy individuals ( 23 , 24 ). Therefore, we hypothesized that the baseline cerebral spontaneous activity patterns of migraineurs could be used as a reliable predictor of acupuncture responsiveness after migraine treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Fu et al [172] performed natural language processing by using a CNN to detect individuals with silent brain infarction using radiological reports, as early detection can be useful for stroke prevention. Using different features extracted from functional MRI data, Yang et al [173] proposed to distinguish between migraine patients and healthy controls (but also between two subtypes of migraine) using an Inception CNN. Finally, MR angiography was used to detect cerebral aneurysms [174,175] using a custom CNN [174] or a ResNet-18 [175].…”
Section: Disease Recognitionmentioning
confidence: 99%